Impact of the COVID-19 Pandemic on the Physical Activity Profile and Glycemic Control Among Qatari Adults With Type 1 Diabetes: Effect of Vaccination Status - Jabbour, Georges; Hermassi, Souhail; Bragazzi, Nicola (Frontiers in Public Health, 2022)
To investigate the impact of COVID-19, as an influent barrier on physical activity (PA) patterns and glycemic control in Qatari adults with type 1 diabetes (T1D). As the COVID-19 vaccine may have a potential impact on an individual’s lifestyle, we also considered this parameter. Physical activity level, the exercise barriers (BAPAD1), anthropometric characteristics, the method of insulin administration, and the last glycated hemoglobin in % were completed by 102 Qatari adults with T1D. Moreover, all patients were asked whether they had “been vaccinated” or had a “fear of being infected by COVID-19”. For the unvaccinated group, weight, BMI and HbA1c (%) were significantly higher than those of vaccinated group (p<0.01) and engaged in less moderate-to-vigorous PA (MVPA) (p < 0.01) per week and had less time in vigorous PA (VPA) (p < 0.01). A significant association between VPA levels and BMI (β=-0.36, p=0.02) and HbA1C (%) (β=-0.22; p=0.03) was reported, and “being vaccinated” was significantly associated with MVPA (β=0.15; p=0.021) and VPA (β=0.28; p=0.032). A higher “Fear of being infected by COVID-19” score was negatively correlated with reduced PA profiles (R2=-0.71 for MVPA; R2=-0.69 for VPA, p < 0.01, respectively). Practicing VPA during the COVID-19 pandemic confer many health benefits for Qatari individual with T1D. As the ‘Fear of being affected by COVID-19” appeared as a potential barrier to PA practices this latter e.g. PA, could likely not be achieved without the participants being vaccinated.